Ti-V-Zr-Cr-Al series ultrahigh-strength near-beta titanium alloy and preparation method thereof
Through the element combination and heat treatment process of Ti-V-Zr-Cr-Al system ultra-high strength near-beta titanium alloy, a two-state structure is formed, which solves the problem that the existing high-strength β titanium alloys are difficult to meet the needs of higher strength and comprehensive performance, and achieves tensile strength and good plasticity of the 1800MPa grade.
Patent Information
- Application Number
- CN202411870687.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-18
AI Technical Summary
When facing the rapid development of the new generation of weapons and equipment, existing high-strength beta titanium alloys are difficult to meet the needs of excellent comprehensive performance such as higher strength, high toughness, damage tolerance, high fatigue performance, low cost and welding.
Ti-V-Zr-Cr-Al ultra-high strength near-beta titanium alloy is used to form a bistate structure through reasonable element combination and heat treatment process, including the primary α phase and the ultrafine secondary α phase, to improve the strength and plasticity of the alloy.
The tensile strength reaches 1800MPa grade, yield strength is greater than 1780MPa, fracture elongation is greater than 3.2%, and uniform elongation is greater than 2.8%, which meets the needs of ultra-high strength and good plasticity.
Smart Images

Figure CN119663051A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium alloy materials, in particular to a Ti-V-Zr-Cr-Al series ultra-high strength near-β titanium alloy and a preparation method thereof. Background Art
[0002] Titanium and its alloys have excellent comprehensive performance matching such as strength, modulus, toughness, high damage tolerance, corrosion resistance and weldability, and have received widespread attention from various industries. At present, high-strength titanium alloys are mainly β-titanium alloys, including some α+β two-phase alloys. Among them, β-titanium alloys have been widely concerned at home and abroad due to their high strength, good cold forming performance and good strength-plasticity matching, especially near-β and metastable β alloys, which have the performance advantages of both α+β two-phase alloys and β alloys. According to the different Mo equivalents, β-type titanium alloys can be divided into four types. When the Mo equivalent is between 0 and 5, it is called β-stable element α+β-type titanium alloy; when the Mo equivalent is between 5 and 10, it is called near-β-type titanium alloy; when the Mo equivalent is between 10 and 30, it is called metastable β-type titanium alloy; when the Mo equivalent is greater than 30, it is called stable β-type titanium alloy.
[0003] For traditional high-strength β titanium alloys such as Ti-1023, Ti-6554, Ti-5553, and Ti-55531, the yield strength of such alloys after aging is generally around 1200-1300 MPa, and their forgings have been successfully used in key parts such as aircraft landing gear and connecting rods. Recently, some scientific and technological personnel have also developed various series of ultra-high-strength titanium alloys, such as 1300MPa Ti-Al-Mo-V-Cr-Zr series, 1400MPa Ti-Al-Mo-V-Cr-Fe series and Ti-Al-Mo-Fe series, 1500MPa Ti-Al-Mo-V-Cr-Zr-Fe-Nb-Sn series and Ti-Al-Mo-V-Cr-Zr-Nb series, and 1600MPa Ti-Al-Mo-V-Cr-Zr-Sn series.
[0004] However, with the rapid development of new generation weapons and equipment such as hypersonic missiles, aircraft, unmanned fighters, high stealth and high maneuverability strategic bombers and new concept weapons, it is urgent to develop ultra-high strength titanium alloy materials to achieve higher strength, high toughness, damage tolerance, high fatigue performance, low cost and weldability and other excellent comprehensive performance requirements to meet the design and use goals of lightweight and long life of new generation weapons and equipment. Therefore, in order to cope with the increasingly harsh use environment and meet the demand for ultra-high strength structural titanium alloys for future high-performance aircraft, it is necessary to carry out research on new 1800MPa ultra-high strength titanium alloys. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a Ti-V-Zr-Cr-Al series ultra-high strength near-β titanium alloy and a preparation method thereof, wherein the strength of the titanium alloy reaches 1800 MPa.
[0006] The present invention is achieved through the following technical solutions: A Ti-V-Zr-Cr-Al ultra-high strength near-β titanium alloy comprises, by mass percentage, 5.0-5.5% Al, 11.0-11.5% V, 2.5-3.0% Cr, 4.5-5.0% Zr, and the remainder Ti and unavoidable impurity elements.
[0007] Preferably, the ultra-high strength near-β titanium alloy has a dual-state structure, including a primary α phase, and a high-density distributed ultrafine secondary α phase and β phase.
[0008] Preferably, the diameter of the primary α phase is 0.75-0.85 μm; the width of the ultrafine secondary α phase is 20-25 nm.
[0009] Preferably, the properties of the ultra-high strength near-β titanium alloy are as follows: Tensile strength R m 1818~1844MPa, yield strength R 0.2 1786~1801MPa, elongation at break A f 3.2~5.1%, uniform elongation A u It is 2.8~3.5%.
[0010] A method for preparing a Ti-V-Zr-Cr-Al series ultra-high strength near-β titanium alloy comprises the following steps: Step 1, preparing alloy ingots; Step 2, forging the alloy ingot, cooling it to the phase transition point and performing upsetting forging, forming a certain amount of primary α phase in the alloy and evenly distributing it in the β grains, and obtaining a titanium alloy forging blank; Step 3, performing solution treatment and aging treatment on the titanium alloy forging billet in sequence to obtain a near-β ultra-high strength titanium alloy with a dual-state structure; The methods of the solution treatment and aging treatment are as follows: The titanium alloy is heated to 10 to 30°C below the β phase transformation point for solution treatment to form a metastable β phase in the alloy; then an aging treatment is performed in the temperature range of 470 to 490°C.
[0011] Preferably, the temperature of the blank forging in step 2 is 1000°C to 1100°C.
[0012] Preferably, the phase transition temperature is 790 5℃.
[0013] Preferably, the solution treatment method is to heat the titanium alloy to a temperature 10 to 30° C. below the β transformation point for solution treatment, and then water cool to room temperature.
[0014] Preferably, the holding time of the aging treatment is 4 hours.
[0015] Preferably, the alloy ingot is obtained by multiple smelting in a vacuum consumable arc furnace.
[0016] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention provides a Ti-V-Zr-Cr-Al ultra-high strength near-β titanium alloy, with a Mo equivalent of 6.7. Compared with the existing high-strength titanium alloys, the alloying element Mo with an extremely high melting point is not added, which is conducive to reducing the difficulty of industrial titanium alloy smelting. At the same time, the β-phase stabilizing element V is not less than 11.0% by mass percentage. The solid solubility of the V element in the α phase is higher than that of Mo, and such a high V element can effectively solid solution strengthen the β phase, and also has a certain α phase strengthening effect, and at the same time reduces the c / a value of the α phase, which is conducive to the slip of the α phase, so that the titanium alloy has a good α / β phase interface compatibility. The Al content ranges from 5.0 to 5.5% by mass percentage. The Al element is conducive to the precipitation of the secondary α phase and prevents the formation of the ω phase. If the content is too low, the solid solution strengthening effect is not obvious, and the phase transition point may be low, which is not conducive to the development of the hot deformation process. If the content is too high, an ordered trend occurs, which is harmful to the fracture toughness of the material TiAl intermetallic compound. At the same time, a high content of neutral element Zr is added to further solid solution strengthen the α phase, increase the critical shear stress of dislocation slip in the α phase, and thus improve the overall strength of the alloy. A certain amount of β phase stabilizing element Cr mainly plays a role in solid solution strengthening of the β phase, improving the plasticity, toughness and hardenability of the material. At the same time, the fast diffusion element Cr is also conducive to the rapid precipitation and nucleation of the α phase, thereby forming an ultra-fine secondary α phase.
[0017] The near-β titanium alloy of the present invention has extremely outstanding mechanical properties. After solution aging, the tensile strength is greater than 1800MPa, the yield strength is greater than 1780MPa, the elongation at break is greater than 3.2%, and the uniform elongation is greater than 2.8%. The microstructure of the near-β titanium alloy is a typical dual-state structure of high-strength titanium alloys, containing a small amount of primary α phase with a diameter of about 0.75 to 0.85μm and a high-density ultrafine secondary α phase with a width of about 20 to 25nm. The plastic effect of the micron-level primary α phase and the strengthening effect of the ultrafine nano-level secondary α phase are combined to simultaneously improve the strength of the alloy and improve the plasticity of the alloy, achieving ultra-high strength while maintaining a certain plasticity, providing a theoretical and material technology basis for promoting the engineering application of ultra-high-strength titanium alloys, further forming my country's aviation titanium alloy material system, and meeting future demand for ultra-high-strength titanium alloy materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 This is a microstructure diagram of the new ultra-high strength near-β titanium alloy of the Ti-V-Zr-Cr-Al series prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.
[0021] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0022] A Ti-V-Zr-Cr-Al ultra-high strength near-β titanium alloy comprises, by mass percentage, 5.0-5.5% Al, 11.0-11.5% V, 2.5-3.0% Cr, 4.5-5.0% Zr, and the remainder Ti and unavoidable impurity elements.
[0023] The Ti-V-Zr-Cr-Al series ultra-high strength near-β titanium alloy has a Mo equivalent of 6.7 and a phase transition temperature of 790 5℃. Compared with the existing high-strength titanium alloys, not adding the alloying element Mo with an extremely high melting point is conducive to reducing the difficulty of industrial titanium alloy smelting. At the same time, the β-phase stabilizing element V is not less than 11.0% by mass, which can effectively solid solution strengthen the β phase, and also has a certain α-phase strengthening effect, and at the same time reduces the c / a value of the α phase, which is conducive to the dislocation slip of the α phase. Adding a higher content of α-stabilizing or neutral elements Al and Zr further solid solution strengthens the α phase, increases the critical shear stress of dislocation slip in the α phase, and thus improves the overall strength of the alloy. A certain amount of β-phase stabilizing element Cr mainly plays a solid solution strengthening role on the β phase. At the same time, the fast-diffusion element Cr is also conducive to the rapid precipitation and nucleation of the α phase, thereby forming an ultrafine secondary α phase.
[0024] The Ti-V-Zr-Cr-Al series ultra-high strength near-β titanium alloy is a near-β ultra-high strength titanium alloy with dual-state structure. The properties of the titanium alloy are as follows: tensile strength R m 1818~1844MPa, yield strength R 0.2 1786~1801MPa, elongation at break A f 3.2~5.1%, uniform elongation A u It is 2.8~3.5%.
[0025] Correspondingly, the present application also provides a method for preparing a Ti-V-Zr-Cr-Al series ultra-high strength near-β titanium alloy, comprising the following steps: Step 1, preparing 5.0-5.5% Al, 11.0-11.5% V, 2.5-3.0% Cr, and 4.5-5.0% Zr by mass percentage, mixing the above raw materials uniformly and then smelting them to obtain an alloy ingot; Specifically, high-purity Al, high-purity V, electrolytic Cr, sponge Zr and sponge Ti are mixed and pressed into electrodes according to designed components, and then smelted twice into alloy ingots in a conventional vacuum consumable arc furnace.
[0026] Step 2: Forging the alloy ingot, cooling it to a phase transition point, and performing repeated upsetting and drawing forging to obtain a titanium alloy forging blank.
[0027] The alloy ingot is forged at a temperature of 1000℃~1100℃, and then the forging temperature is gradually reduced to near the phase transformation point of 790℃ for repeated upsetting and drawing forging to achieve static recovery and dynamic recrystallization of its microstructure. After final forging, a certain amount of primary α phase is uniformly distributed in the fine β grains to obtain an ultra-high strength titanium alloy forging billet.
[0028] Step 3: performing solution treatment and aging treatment on the titanium alloy forging billet in sequence to obtain a near-β ultra-high strength titanium alloy with a dual-state structure.
[0029] Solution treatment: The titanium alloy is heated to 10-30°C below the β phase transformation point for solution treatment, and then water-cooled to room temperature, that is, solution treatment in the temperature range of 760-780°C forms a metastable β phase. A small amount of primary α phase can inhibit the excessive growth of β grains, and then aging treatment is performed.
[0030] Aging treatment: High temperature aging is carried out at a temperature range of 470-490°C for 4 hours to induce the dispersion and precipitation of fine secondary α phase, thereby achieving precipitation strengthening and finally obtaining a near-β ultra-high strength titanium alloy with a dual-state structure.
[0031] After solution aging, the near-β titanium alloy presents a typical dual-state structure, containing a small amount of primary α phase with a diameter of about 0.75-0.85μm and a high-density ultrafine secondary α phase with a width of about 20-25nm. The plastic effect of the micron-level primary α phase and the strengthening effect of the ultrafine nano-level secondary α phase are combined to simultaneously improve the strength and plasticity of the alloy, and have extremely outstanding mechanical properties: tensile strength greater than 1800MPa, yield strength greater than 1780MPa, elongation at break greater than 3.2%, and uniform elongation greater than 2.8%. The near-β titanium alloy maintains a certain degree of plasticity while also having ultra-high strength, providing a theoretical and material technology basis for promoting the engineering application of ultra-high-strength titanium alloys, further forming my country's aviation titanium alloy material system, and meeting future demand for ultra-high-strength titanium alloy materials.
[0032] Example 1 A method for preparing a Ti-V-Zr-Cr-Al series ultra-high strength near-β titanium alloy comprises the following steps: Step 1: Al 5.1%, V 11.3%, Cr 2.7%, Zr 4.7%, and the balance Ti and inevitable impurities are mixed and pressed into electrodes, and then smelted twice in a vacuum consumable arc furnace into alloy ingots.
[0033] The above raw materials include high-purity Al, high-purity V, electrolytic Cr, sponge Zr and sponge Ti.
[0034] Step 2: The alloy ingot is forged at 1050°C, and then the forging temperature is gradually reduced to near the phase transformation point of 790°C for repeated upsetting and drawing forging to achieve static and dynamic recrystallization of its microstructure. After final forging, a certain amount of primary α phase is uniformly distributed in fine β grains to obtain an ultra-high strength titanium alloy forging billet.
[0035] Step 3: performing solution treatment and aging treatment on the titanium alloy forging blank.
[0036] The metastable β phase is formed by solution treatment in the temperature range of 770℃, and a small amount of primary α phase can inhibit the excessive growth of β grains. Then, high-temperature aging is performed in the temperature range of 480°C to induce the dispersion and precipitation of fine secondary α phase, thereby achieving precipitation strengthening and finally obtaining an ultra-high-strength near-β titanium alloy.
[0037] The dual-state microstructure of the ultra-high strength near-β titanium alloy is as follows Figure 1 As shown, the alloy of this embodiment contains a small amount of primary α phase with a diameter of about 0.79 μm and a high-density distributed ultrafine secondary α phase with a width of about 21 nm, and the rest is β phase.
[0038] The Ti-V-Zr-Cr-Al ultra-high strength near-β titanium alloy prepared in this embodiment is subjected to room temperature tensile property test according to GB / T228.1-2010 standard after heat treatment, and its tensile properties are: tensile strength R m The yield strength R is 1844MPa. 0.2 The elongation at break is 1801MPa, and the elongation at break is A f The uniform elongation is 5.1%. u The alloy of this embodiment has ultra-high strength while maintaining a certain plasticity.
[0039] Example 2 A method for preparing a Ti-V-Zr-Cr-Al series ultra-high strength near-β titanium alloy comprises the following steps: Step 1: Al 5.5%, V 11.0%, Cr 2.5%, Zr 5.0%, and the balance Ti and inevitable impurities are mixed and pressed into electrodes, and then smelted twice in a vacuum consumable arc furnace into alloy ingots.
[0040] The above raw materials include high-purity Al, high-purity V, electrolytic Cr, sponge Zr and sponge Ti.
[0041] Step 2: The alloy ingot is forged at 1000°C, and then the forging temperature is gradually reduced to near the phase transformation point of 790°C for repeated upsetting and drawing forging to achieve static and dynamic recrystallization of its microstructure. After final forging, a certain amount of primary α phase is uniformly distributed in fine β grains to obtain an ultra-high strength titanium alloy forging billet.
[0042] Step 3: performing solution treatment and aging treatment on the titanium alloy forging blank.
[0043] Solution treatment: Solution treatment in the temperature range of 780℃ forms a metastable β phase, and a small amount of primary α phase can inhibit the excessive growth of β grains; Aging treatment: High temperature aging in the temperature range of 470℃ induces the dispersion and precipitation of fine secondary α phase, thereby achieving precipitation strengthening and finally obtaining an ultra-high strength near-β titanium alloy.
[0044] The dual-state microstructure of the ultra-high strength near-β titanium alloy is as follows Figure 1 As shown, the alloy of this embodiment contains a small amount of primary α phase with a diameter of about 0.85 μm and a high-density distributed ultrafine secondary α phase with a width of about 20 nm, and the rest is β phase.
[0045] The Ti-V-Zr-Cr-Al ultra-high strength near-β titanium alloy prepared in this embodiment is subjected to room temperature tensile property test according to GB / T228.1-2010 standard after heat treatment, and its tensile properties are: tensile strength R m The yield strength R is 1844MPa.0.2 The elongation at break is 1801MPa, and the elongation at break is A f The uniform elongation is 5.1%. u The alloy of this embodiment has ultra-high strength while maintaining a certain plasticity.
[0046] Example 3 A method for preparing a Ti-V-Zr-Cr-Al series ultra-high strength near-β titanium alloy comprises the following steps: Step 1: Al 5.0%, V 11.5%, Cr 3.0%, Zr 4.5%, and the balance Ti and inevitable impurities are mixed and pressed into electrodes, and then smelted twice in a vacuum consumable arc furnace into alloy ingots.
[0047] The above raw materials include high-purity Al, high-purity V, electrolytic Cr, sponge Zr and sponge Ti.
[0048] Step 2: The alloy ingot is forged at 1100°C, and then the forging temperature is gradually reduced to near the phase transformation point of 790°C for repeated upsetting and drawing forging to achieve static and dynamic recrystallization of its microstructure. After final forging, a certain amount of primary α phase is uniformly distributed in fine β grains to obtain an ultra-high strength titanium alloy forging billet.
[0049] Step 3: performing solution treatment and aging treatment on the titanium alloy forging blank.
[0050] Solution treatment: Solution treatment in the temperature range of 760℃ forms a metastable β phase, and a small amount of primary α phase can inhibit the excessive growth of β grains; Aging treatment: High temperature aging in the temperature range of 490℃ induces the dispersion and precipitation of fine secondary α phase, thereby achieving precipitation strengthening and finally obtaining an ultra-high strength near-β titanium alloy.
[0051] The dual-state microstructure of the ultra-high strength near-β titanium alloy is as follows Figure 1 As shown, the alloy of this embodiment contains a small amount of primary α phase with a diameter of about 0.75 μm and a high-density distributed ultrafine secondary α phase with a width of about 25 nm, and the rest is β phase.
[0052] The Ti-V-Zr-Cr-Al ultra-high strength near-β titanium alloy prepared in this embodiment is subjected to room temperature tensile property test according to GB / T228.1-2010 standard after heat treatment, and its tensile properties are: tensile strength R m The yield strength is 1818MPa, and the yield strength R 0.2 The elongation at break is 1786MPa. f The uniform elongation is 3.2%. u The alloy of this embodiment has ultra-high strength while maintaining a certain plasticity.
[0053] Table 1 Performance test results of Ti-V-Zr-Cr-Al ultra-high strength near-β titanium alloy prepared in Examples 1-3
[0054] As can be seen from Table 1, the embodiment of the present invention is a new type of ultra-high strength near-β titanium alloy of the Ti-V-Zr-Cr-Al series with a dual-state structure, which has a tensile strength of more than 1800MPa, a yield strength of 1780MPa, an elongation at break greater than 3.2%, and a uniform elongation greater than 2.8%. The above results show that the new type of ultra-high strength near-β titanium alloy of the Ti-V-Zr-Cr-Al series of the present invention has ultra-high strength while maintaining a certain plasticity, especially a tensile strength of 1800MPa, which has extremely high value and broad prospects for further promoting the application of near-β titanium alloys in the fields of aerospace, energy industry, etc. that require ultra-high strength service performance.
[0055] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A Ti-V-Zr-Cr-Al ultra-high strength near-β titanium alloy, characterized in that: Calculated by mass percentage, it includes 5.0-5.5% Al, 11.0-11.5% V, 2.5-3.0% Cr, 4.5-5.0% Zr, and the balance is Ti and inevitable impurity elements.
2. The Ti-V-Zr-Cr-Al ultra-high strength near-β titanium alloy according to claim 1, characterized in that: The ultra-high strength near-β titanium alloy is a dual-state structure, including a primary α phase, and ultra-fine secondary α phase and β phase distributed in high density.
3. The Ti-V-Zr-Cr-Al ultra-high strength near-β titanium alloy according to claim 2, characterized in that: The diameter of the primary α phase is 0.75-0.85 μm; the width of the ultrafine secondary α phase is 20-25 nm.
4. The Ti-V-Zr-Cr-Al ultra-high strength near-β titanium alloy according to claim 1, characterized in that: The properties of the ultra-high strength near-β titanium alloy are as follows: Tensile strength R m 1818~1844MPa, yield strength R 0.2 1786~1801MPa, elongation at break A f 3.2~5.1%, uniform elongation A u It is 2.8~3.5%.
5. A method for preparing a Ti-V-Zr-Cr-Al ultra-high strength near-β titanium alloy according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1, preparing alloy ingots; Step 2, forging the alloy ingot, cooling it to the phase transition point and performing upsetting forging, forming a certain amount of primary α phase in the alloy and evenly distributing it in the β grains, and obtaining a titanium alloy forging blank; Step 3, performing solution treatment and aging treatment on the titanium alloy forging billet in sequence to obtain a near-β ultra-high strength titanium alloy with a dual-state structure; The methods of the solution treatment and aging treatment are as follows: The titanium alloy is heated to 10 to 30°C below the β phase transformation point for solution treatment to form a metastable β phase in the alloy; then an aging treatment is performed in the temperature range of 470 to 490°C.
6. The method for preparing a Ti-V-Zr-Cr-Al series ultra-high strength near-β titanium alloy according to claim 5, characterized in that: The temperature of the blank forging in step 2 is 1000°C to 1100°C.
7. The method for preparing a Ti-V-Zr-Cr-Al series ultra-high strength near-β titanium alloy according to claim 5, characterized in that: The phase transition temperature is 790 5℃.
8. The method for preparing a Ti-V-Zr-Cr-Al series ultra-high strength near-β titanium alloy according to claim 5, characterized in that: The method of the solid solution treatment is to heat the titanium alloy to a temperature 10 to 30° C. below the β phase transformation point for solid solution treatment, and then water cool it to room temperature.
9. The method for preparing a Ti-V-Zr-Cr-Al series ultra-high strength near-β titanium alloy according to claim 5, characterized in that: The holding time of the aging treatment is 4 hours.
10. The method for preparing a Ti-V-Zr-Cr-Al series ultra-high strength near-β titanium alloy according to claim 5, characterized in that: The alloy ingot is obtained by multiple smelting in a vacuum consumable arc furnace.
Citation Information
Patent Citations
High-strength and high-plasticity metastable-state beta-type titanium alloy and preparation method thereof
CN113862514A
HIGH-STRENGTH alpha-beta TITANIUM ALLOY
JP2005076098A
Material for the manufacture of high-strength fasteners and method for producing same
US20240150869A1
Cited By
Smelting method of homogeneous ultrahigh-strength titanium alloy cast ingot
CN122081699A